The Simplified of Suspended Sediment Measurement Method in Natural River (Case study of Kuning River in Yogyakarta, Indonesia) - Bambang Agus Kironoto; Bambang Yulistiyanto; Bangun Giarto; Mariatul Kiptiah; Muhammad Lutfi Tantowi (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2019)
The accumulation of suspended sediment reduces the capacity in the river and deteriorates the water quality. Kuning River in Yogyakarta is one of the main rivers in Yogyakarta, Indonesia, which is currently facing the issue of suspended sediments. To reduce the effect of suspended sediment and determine a preventive measure, hence, it is necessary to study the characteristics of the suspended sediment flow. Therefore, this study aims to investigate the suspended sediment flow characteristics, i.e. the velocity, and the concentration profiles at specific points in the transverse direction of the channel as well as the correlation of the suspended sediment discharge. Thirty (30) profiles of velocity and suspended sediment concentration were measured at six different points along the Kuning River. Opcon probe was used to measure suspended sediment concentration, while the propeller current meter was used to measure mean point-velocity profiles. Results of this study show the suspended sediment discharge ratio, defined as are higher in the middle part of the channel than the one near the edge of the channel. The position of z/B where the values of 1 occurs at z/B = 0,19 and z/B = 0,75, which depend on the irregularity of the channel cross-sections. For practical purposes, the depth-averaged velocity and suspended sediment concentration can be determined from 1, 2 and/or 3 points measurement at y = 0,2D, 0,4D and 0,8D.